Impact of Heat Transfer and Inclined MHD on A Non-Uniform Inclined Asymmetrical Channel with Couple Stress Fluid Through A Porous Medium - Abdulhussein, Hanaa; Abdulhadi, Ahmed M. (Iraqi Journal of Science, 2023)
The goal of this study is to investigate the effects of heat transfer on a non-uniform inclined asymmetrical channel with couple stress fluids via a porous medium using incline magnetohydrodynamics. The governing equation is studied while using low Reynolds approximations and long-wavelength assumptions. Mathematical expressions for (pressure gradient), (temperature), (axial velocity), (heat temperature coefficient), and (stream function). A precise set of values for the various parameters in the present model has been used. The mathematical expressions for axial velocity, stream function, pressure gradient, and pressure rise per wavelength have been derived analytically. "MATHEMATICA" is used to present the computational results in the form of graphs. It has been noticed that both the pressure rise and the pressure gradient decrease with the rise of the inclination magnetic field angle and Darcy number, while as the Grashof number increases, the pressure gradient reduces and the pressure also increases. According to this study, the heat transfer coefficient and temperature rise when the Brinkman number and the Hartman number are up. As the Hartman number and couple stress increase, the incidence of trapped boluses diminishes in size and vanishes in the direction downstream. The bolus size can also be increased by raising the non-uniform channel’s Darcy number.